Karl Raimud Popper dan Auguste Comte (Suatu Tinjauan Tematik Probelm Epistemologi dan Metodologi) - Aziz, Ichwan Supandi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
Epistemological and methodological basic of science are very important to reduce the negative aspects of scienctific development. This paper was written with major theme both Auguste Comte verifiable and Karl Raimud Popper falsifiable methodes. They introduced the important epistemology and methodology which shoul be applicated to the scientific progress in order to make better result.